2002
DOI: 10.1034/j.1600-0714.2002.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of hepatocyte growth factor, transforming growth factor‐β and their receptors in epithelial odontogenic tumors

Abstract: Immunohistochemical localization of HGF, TGF-beta and their receptors in tooth germs and epithelial odontogenic tumors supports the hypothesis that HGF and TGF-beta act on epithelial cells via paracrine and autocrine mechanisms. Altered expression of the agents in these epithelial odontogenic tumors, especially subtypes of ameloblastomas, AOTs and COCs, suggests that HGF and TGF-beta signaling might affect differentiation of neoplastic odontogenic epithelial cells. Activated HGF/c-Met pathway and reduced TGF-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
27
1
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 46 publications
7
27
1
4
Order By: Relevance
“…This finding may be closely related to the angiogenesis and invasive biological behavior of ameloblastomas, corroborating the studies of Chen et al [1] and Kumamoto et al [13] who have already suggested that VEGF is an important mediator of angiogenesis in these epithelial odontogenic tumors. Its up-regulation might be associated with malignant neoplastic changes of odontogenic epithelial cells.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This finding may be closely related to the angiogenesis and invasive biological behavior of ameloblastomas, corroborating the studies of Chen et al [1] and Kumamoto et al [13] who have already suggested that VEGF is an important mediator of angiogenesis in these epithelial odontogenic tumors. Its up-regulation might be associated with malignant neoplastic changes of odontogenic epithelial cells.…”
Section: Discussionsupporting
confidence: 79%
“…These processes play a key role in repairing and remodeling bone during development and, in odontogenic tumors, they promote bone resorption [13]. Numerous observations have shown that VEGF is generated from a variety of cells inside or in the close vicinity of blood vessels under many physiological or pathological conditions and it acts as a major player in the initial step of angiogenesis [13].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, overexpression of the EGFR family members, Her-2 and Her-3, has been identified in keratocystic odontogenic tumors (26,67). TGF-β and its receptors are expressed in many types of odontogenic tumors, suggesting that they have an important role in cell differentiation and matrix formation via regulation or dysregulation of epithelial-mesenchymal interactions (24,66,(68)(69)(70). HGF and its receptor c-Met, essential for morphogenesis of tooth germs, are expressed in many types of odontogenic tumors, suggesting that they affect epithelialmesenchymal interactions not only in developing teeth but also in neoplastic odontogenic tissues (24,70).…”
Section: Growth Factorsmentioning
confidence: 99%
“…TGF-β and its receptors are expressed in many types of odontogenic tumors, suggesting that they have an important role in cell differentiation and matrix formation via regulation or dysregulation of epithelial-mesenchymal interactions (24,66,(68)(69)(70). HGF and its receptor c-Met, essential for morphogenesis of tooth germs, are expressed in many types of odontogenic tumors, suggesting that they affect epithelialmesenchymal interactions not only in developing teeth but also in neoplastic odontogenic tissues (24,70). Increased expression of HGF and c-Met in ameloblastic carcinomas and clear cell odontogenic carcinomas implies that HGF signaling might be associated with the malignant potential of epithelial odontogenic tumors (70).…”
Section: Growth Factorsmentioning
confidence: 99%
See 1 more Smart Citation